Heathen, Hindoo, Hindu: American representations of India, 1721-1893 - Altman, Michael J. (Oxford University Press, 2017)
Heathens and Hindoos in early America -- Missionaries, Unitarians, and Raja Rammohun Roy -- Hindoo religion in American National Culture -- Transcendentalism, Brahmanism, and universal religion --The theosophical quest for occult power -- Putting the "Religions" in world's Parliament of Religions.